MENGGUGAT NARASI BESAR DAN SIMULAKRA PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Yeterina Widi Nugrahanti (Dinamika Akuntansi Keuangan dan Perbankan, 2016)
The purpose of this article is to describe Corporate Social Responsibility(CSR) Disclosure using postmodern perspectives, Lyotard’s and Jean Baudrillard’s thinking. From Lyotard’s thinking, CSR disclosure can be viewed as grand narration used to camouflage real social and environmental problems.CSR disclosure guideliness arranged by Global Reporting Initiative (GRI) is a form of universalims that strongly opposed by postmodernism. CSR disclosure practices that accommodate Indonesian cultures and values will be able to break grand narration in CSR disclosure. From Baudrillard perspective, CSR disclosure can be viewed as simulacrum. The simulacrum is shown by (a) the disconnect between reality and its representations, especially the lack of tranparancy in negative business impact disclosures; (b) The control and manipulation of information, and (c) the proliferation of misleading images. To break the CSR disclosure simulacra, it takes CSR concept that based on love, which are love to God, love to human being and love to nature.  Keywords: corporate social responsibility disclosure, posmodernism, grand naration, simulacra